Development of nano-satellite-MEMs based ADCS sensors - Ang, Wei Cheng (2011)
Being inspire by the completion of the micro-satellite XSAT program, and currently waiting for the launch, NTU has started another program to develop a pico- and nano-satellite pair VELOX-I. This program includes many FYP projects working on the various sub-systems of a satellite. For a satellite to determine and control its location and orientation in space, the Attitude Determination and Control System (ADCS) is an essential sub-system for the task. This project focuses on the GPS receiver in the ADCS which determines the position and velocity with respect to the vertical axis of the satellite. The position and velocity direction will allow the satellite to orientate itself perpendicular to keep the satellite to stay in course of the flight plan. In this project, software implementation between GPS receiver and micro-controller has been implemented. In addition, performance test and error analysis of the GPS receiver has been conducted. This information is important as how the characterises of the GPS receiver response in real time operation environment. The position of error of the GPS initially approximately 69.14 metres but were reduced by 50% with the implementation of RF combiner with two GPS antenna. This will allows the satellite location do not deviate much from the actual location. The GPS receiver and the micro-controller has been tested in the outdoor and proven function satisfactory.